The invasion ecology of Nymphaea mexicana Zucc. (Mexican Water lily) in South Africa - Naidu, Prinavin (Rhodes University, Faculty of Science, Botany Department, 2019)
The Mexican water lily, Nymphaea mexicana Zuccarini, is an aquatic perennial, native to southern USA and Mexico, and has been introduced to South Africa via the ornamental plant trade. This species has rapid growth rates and becomes weedy in dams, ponds and rivers. It is currently listed as a NEM:BA category 1b invasive plant in South Africa. One possible management measure for this weed is biological control, but it is a novel target because no biological control programme has been initiated against it anywhere in the world. This study is intended as a baseline for the biological control programme against this plant in South Africa. Assessing the population structure and mode of reproduction of invasive alien plants is an imperative aid to determining if biological control is a suitable management option. Using amplified fragment length polymorphism (AFLP) molecular markers, I compared the amount of genetic variability and differentiation of N. mexicana in its native range (USA), and invasive range (South Africa). Results indicated a large genetic distance between populations in the USA and South Africa, compared to populations within each country. The genetic variability of the invasive populations was higher than that found in the native distribution. This could be due to hybridization in the introduced range, and/or multiple introductions from different source populations. Differences in the morphology of N. mexicana plants in the invasive range and South Africa were also observed which confirm the results of the genetic analyses. I also assessed the reproductive mode of N. mexicana cultivars/hybrids by conducting breeding system experiments and field pollinator studies. Results indicated that the cultivars are sterile, suggesting that the primary mode of reproduction is asexual via fragmentation of tubers. The main pollinators that were found to be associated with the cultivars in South Africa were honeybees, sweat bees, flies and beetles. These insect groups were the same as those that were observed in another study which was conducted on the pollinators associated with the pure N. mexicana in the native range in southern USA. Mechanical and chemical control of N. mexicana and its multiple genotypes have been applied but have not been efficient due to the fast regeneration of shoots, especially in summer. Therefore, these two management options are not long"“term solutions and will also be costly due to the widespread occurrence of the hybrids in South Africa. Thus the only cost"“effective, environmentally friendly, self"“sustainable and long"“term management option is biological control. The significant divergence between native and invasive populations of N. mexicana, as well as the possibility of numerous invasive cultivars, may limit future prospects of biological control of this species. However the differences in the root structures between native South African waterlilies, such as N. lotus and N. nouchali, and the introduced waterlilies, such as N. mexicana and its associated hybrids, may play a pivotal role in the success of biological control of the N. mexicana hybrid complex in South Africa. Natural enemies which feed on the hard tuberous roots of N. mexicana and its hybrids, as opposed to the soft bulbs of the native N. nouchali and N. lotus, should be prioritised.
Keywords: Nymphaea Mexicana zuccarini; Nymphaea; Nymphaea -- Biological control -- South Africa; Water lilies; Nymphaea -- Ecology -- South Africa; Water lilies -- Biological control -- South Africa; Invasive plants -- Biological control -- South Africa; Aquatic weeds -- Biological control -- South Africa; Water lilies -- Ecology -- South Africa